Pengaruh Model Pembelajaran Remap STAD Terhadap Pemberdayaan Keterampilan Literasi Sains Peserta Didik - Ferry Irawan; Siti Zubaidah; Sulisetijono Sulisetijono (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Science literacy skills are basic skills that must be possessed by students as a provision to be able to integrate their basic understanding related to the coherent scientific concepts. This study aims to look at the effectiveness of the Remap STAD learning model to empower science literacy skills. The study was classified as quasy experimental research using Non equivalent pretest-posttest control group design. The population of 234 students includes students of class XI Science with a total of seven classes. The sample used was selected through the equivalence test. The instrument uses an essay test by disregarding indicators of scientific literacy skills. Data were analyzed using One Way Anacova Test. The results obtained that the Remap STAD learning model contributes to empower students' scientific literacy skills. Abstrak: Keterampilan literasi sains merupakan keterampilan dasar yang harus dimiliki peserta didik agar mampu mengintegrasikan pemahaman dengan konsep ilmiah. Penelitian ini bertujuan untuk melihat pengaruh model pembelajaran Remap STAD terhadap pemberdayaan keterampilan literasi sains. Penelitian ini tergolong penelitian quasy experiment menggunakan Non equivalent pretest-posttest control group design. Populasi berjumlah 234 siswa mencakup siswa kelas XI IPA dengan total tujuh kelas. Sampel yang digunakan dipilih melalui hasil uji kesetaraan. Instrumen menggunakan tes esai mengacuh pada indikator keterampilan literasi sains. Analisis menggunakan One Way Anacova Test dan hasilnya model pembelajaran Remap STAD berpengaruh terhadap keterampilan literasi sains peserta didik.